The Association of (effective and ineffective) analgesic intake, pain interference and heart rate variability in a cross-sectional occupational sample - Koenig, Julian; Fischer, Joachim E. (Pain medicine, 2015)
ObjectivePersistent pain is associated with dysfunction of the autonomic nervous system, in particular a loss of vagal inhibitory control, that can be indexed by decreased vagally mediated heart rate variability (vmHRV). Effective treatment (e.g., analgesic self-medication) may lead to a restoration of vmHRV. The objective of this article was to further explore the relationship of pain and vagal control and to investigate the effect of analgesic self-medication on the association of vmHRV and pain.MethodsWe used a large cross-sectional data set on pain ratings and analgesic intake from the Mannheim Industrial Cohort Study for secondary analysis. The root mean square of successive differences, a measure of vmHRV corresponding to the parasympathetic regulation of the heart, was derived from 24-hour electrocardiogram recordings.ResultsThe frequency of analgesic intake and interference of pain are significantly associated. Individuals that report greater pain interference with their normal work routine (including both work outside the home and housework) and frequent analgesic intake have significantly lower vmHRV. Subjects with ineffective analgesic intake (reporting great pain interference and high frequent analgesic intake) had the lowest vmHRV. Individuals effectively taking analgesics (reporting no or low pain interference and high frequent analgesic intake) showed greater vmHRV compared to those ineffectively taking. Analysis revealed significant differences and linear trends on vmHRV between all groups.ConclusionIn line with previous research, vmHRV is inversely associated with pain interference. Analgesic intake mediates the association of vmHRV and pain. Effective analgesic self-medication may lead to a restoration in vmHRV. These results further support the vagus nerve as an objective indication of pain severity and treatment efficacy in patients with persistent pain.
Gesehen am 04.10.2017